2022
DOI: 10.21608/aimj.2022.118648.1815
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between the effect of letrozole versus letrozole with Metformin in treatment of anovulation in overweight women.

Abstract: Background: Ovulation disorders account for around 30% of infertility and are frequently accompanied by irregular menstrual (oligomenorrhoea) or an absence of periods (amenorrhea). Several therapies are easy and efficient, so couples might only require limited contact with doctors. This makes it simpler for a couple to retain a private love connection than in stressful situations. Aim of the work:To assess the impact of letrozole with letrozole plus metformin as an ovulation inducing agent in anovulatory overw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…According to Amooee et al (3) , patients who took metformin had higher adverse effects than those who received chromium picolinate. Also, Rohaim et al (11) demonstrated that there was no significance among the groups of study according to nausea and vomiting. Furthermore, metformin treatment was correlated to a greater frequency of nausea (P = 0.028), indigestion (P = 0.039), diarrhea (P = 0.001), vomiting (P = 0.001), & abdominal pain (P = 0.002), whereas chromium picolinate was correlated with headache (P = 0.001) & lack of appetite (P = 0.018) (14) .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…According to Amooee et al (3) , patients who took metformin had higher adverse effects than those who received chromium picolinate. Also, Rohaim et al (11) demonstrated that there was no significance among the groups of study according to nausea and vomiting. Furthermore, metformin treatment was correlated to a greater frequency of nausea (P = 0.028), indigestion (P = 0.039), diarrhea (P = 0.001), vomiting (P = 0.001), & abdominal pain (P = 0.002), whereas chromium picolinate was correlated with headache (P = 0.001) & lack of appetite (P = 0.018) (14) .…”
Section: Resultsmentioning
confidence: 98%
“…The findings of our study are corroborated by Amooee et al (3) who stated that there was no significance among the groups of study according to age and length. Also, Rohaim et al (11) demonstrated that there was no significance among the groups of study according to age, parity, and BMI.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations